The Dialogical Self: Investigating Multiple ‘I’ Positions in Sarah Glidden's and Guy Delisle's Select Graphic Memoirs - Fatima, Samreen (South Asian Journal of Social Sciences and Humanities, 2022)
Graphic memoirs have gained a critical attention only after Spiegalman’s foundational work Maus. The merge of images and text produces unique literary experience for the readers. The paper is an attempt to explore the gripping graphic memoirs of Sarah Glidden and Guy Delisle and the emergence of dialogical self and multiple I positions within the text. Dialogical Self theory is a research module that showcases the self expanding its definition. Unlike the Cartesian approach to self that believes its sharp distinction with other. Dialogical Self theory proposes the idea of a heterogeneous and dense self where the self involves in a dialogue with itself. This gives space for multiplicity of voices/narrations within the self and thus bridges the gap between self and other. How to understand Israel in 60 days or less and Jerusalem: chronicles from the holy city are works centered on the pertaining Israeli-Palestinian conflict. The creative format of a comic allows the respective authors to illustrate the different selves in a single panel. It fosters the concept of other as an extended self on the subjective level. The paper investigates how the protagonists Sarah and Delisle go on a trip to Jerusalem and gains a better understanding of themselves and of others. Keywords: graphic memoirs, dialogical self, multiple I position, self, other, Israeli Palestinian conflict
Keywords: graphic memoirs; dialogical self; multiple ‘I’ position; self; other; Israeli Palestinian conflict